Study on Stress Depending on HSS Panel Joint Method in Automobiles - et. al., Woonsang Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A vehicle to which a body panel reinforced by repairing an automobile body is applied must be welded or joined by a method suitable for the panel material so as to prevent corrosion of the panel and ensure rigidity of the body structure. As a result of studying the stress by the joining method of HSS and UHSS panels, it was confirmed that the welding method was performed in parallel and the joining method was superior to the simple joining method from the tensile stress strength. In addition, spot welding and post-bonding rivets were used as an efficient joining method that can minimize the deformation of the material properties of the vehicle body panel, prevent corrosion, and maximally maintain the rigidity of the vehicle body structure..